Perceptions of termites in urban areas of semiarid Brazil - Maria Avany Bezerra Gusmão; Ana Marcia Silva Barbosa; Antonio Paulino Mello; José Valberto Oliveira; Adrianne Teixeira Barros (Biotemas)
Perception of termites in urban areas of semiarid Brazil. Termites are present in the daily life of most people, although they usually evoke a sense of strong dislike, especially in populations of urban areas. This study sought to analyze the perception of these insects in human populations in urban areas in the towns of Fagundes (A1) and Pocinhos (A2), in Paraíba state, Brazil. Semi-structured questionnaires were answered by 100 residents in these two areas, following both synchronic and diachronic situations. In spite of the fact that most of the interviewees (64% in A1 and 72% in A2) were able to identify termites by morphology and had knowledge of use for treating eight types of human diseases, very few understood their ecological roles in nature. Attempts to eliminate termites from human environments were linked to the popular belief that these animals are sources of bad luck. Twenty-two percent of the interviewees in A1 and 8% in A2 believe that termites are capable of doing damage or harm, of having a foul smell, and/or of containing pus.In this sense, academic studies are important because they can inform people of the ecological roles of termites in natural and urban environments, while demystifying the termite as an agent of fear and destruction.